The strange bird : a Borne story - VanderMeer, Jeff (MCD/Farrar, Straus and Giroux, 2018)
The Strange Bird is a new kind of creature, built in a laboratory--she is part bird, part human, part many other things. But now the lab in which she was created is under siege and the scientists have turned on their animal creations. Flying through tunnels, dodging bullets, and changing her colors and patterning to avoid capture, the Strange Bird manages to escape. But she cannot just soar in peace above the earth. The sky itself is full of wildlife that rejects her as one of their own, and also full of technology--satellites and drones and other detritus of the human civilization below that has all but destroyed itself. And the farther she flies, the deeper she finds herself in the orbit of the Company, a collapsed biotech firm that has populated the world with experiments both failed and successful that have outlived the corporation itself